(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the political TV-advertisement as the particular type of texts is characterized, it’s communicating aims are determined. The author proves the connection of political TV-advertisement’s composition, language peculiarities and the purpose of these texts to influence the mass consciousness.